Mental Health, Alcohol and Substance Use of Refugee Youth - Vasic, Jelena; Grujicic, Roberto; Toskovic, Oliver; Pejovic Milovancevic, Milica (Frontiers in Psychiatry, 2021)
Adolescence is a life period in which the propensity to first-time drug and substance use is the highest. The population of refugee youth, especially unaccompanied minors, may be particularly vulnerable. This study aims to explore the prevalence of alcohol and substance use among young refugees along with the indicators of psychological difficulties. It is based on a sample of 184 children and adolescents aged 11 to 18 years old, residing at two refugee centers in the Republic of Serbia. Out of 184 participants, the majority is male (N=155; 84.29%), while 29 (15.71%) is female. More than a half of participants (53.3%) displayed significant symptoms of PTSD. We find that 50% consume energy drinks, 28% use tobacco; 13% use alcohol; 4.6% use marijuana; 1.7% use LSD, amphetamines, glue, tranquilizers and cocaine. Female respondents were more frequently expressing emotional difficulties (p<0.05) while male participants were more frequent users of alcohol or substances (p<0.01). Younger children were more frequently expressing symptoms of hyperactivity and prosocial behavior, while they were less frequently using substances. There’s also a significant negative correlation of duration of education to proneness to substance abuse. The burden of migration contributes to proneness to substance use, as a consequence of scarce coping resources and the stress of adjusting. Migrants are vulnerable to substance use, since some of them have commonly witnessed and/or personally experienced pre- and post-migration stress and trauma, including loss of homes and livelihoods, violence, torture and family separation. Preventive programs need to focus on substance abuse among this vulnerable population.